Levels of reducing sugars in eight Kenyan potato cultivars as influenced by stage of maturity and storage conditions - Abong’, George O.; Okoth, Michael W.; Karuri, Edward G.; Kabira, Jackson N.; Mathooko, Francis M. (Journal of Animal & Plant Sciences, 2012)
The cultivar, harvest time and storage method affect reducing sugars content of potato, which in turn influences the processing quality of French fries. Eight Kenyan potato cultivars (Tigoni, Desiree, Dutch Robyjn, Kenya Karibu and Kenya Sifa) and three advanced clones (393385.47, 391696.96 and 393385.39) were studied to determine their suitability for the chipping industry, and to determine the effect of harvesting time and storage conditions on their processing quality. Early harvesting of tubers resulted in significantly higher (P≤0.05) levels of reducing sugars (0.33-0.45 %) than harvesting at maturity (0.15-0.37 %). No significant change (P>0.05) occurred in the reducing sugar content when tubers were stored at ambient air conditions (15-19 oC/86-92 % RH) for up to 12 weeks. In cold storage (4 oC/95 % RH), tubers of all the cultivars accumulated more reducing sugars and none was suitable for chipping even after reconditioning for up to 3 weeks at ≥15 oC. Cold stored potatoes may, however, be suitable for mashing and or general home use. The information obtained in this study will inform Kenyan farmers and processors regarding the appropriate harvesting time and storage conditions for potatoes produced for chipping.
Keywords: Reducing sugars; Cultivars; Harvest time; Storage temperature; Reconditioning